Actiflagelin, a new sperm activator isolated from Walterinnesia aegyptia venom using phenotypic screening - El-Aziz,Tarek Mohamed Abd (2018)
Abstract Background Sperm contains a wealth of cell surface receptors and ion channels that are required for most of its basic functions such as motility and acrosome reaction. Conversely, animal venoms are enriched in bioactive compounds that primarily target those ion channels and cell surface receptors. We hypothesized, therefore, that animal venoms should be rich enough in sperm-modulating compounds for a drug discovery program. Our objective was to demonstrate this fact by using a sperm-based phenotypic screening to identify positive modulators from the venom of Walterinnesia aegyptia. Methods Herein, as proof of concept that venoms contain interesting compounds for sperm physiology, we fractionated Walterinnesia aegyptia snake venom by RP-HPLC and screened for bioactive fractions capable of accelerating mouse sperm motility (primary screening). Next, we purified each compound from the positive fraction by cation exchange and identified the bioactive peptide by secondary screening. The peptide sequence was established by Edman sequencing of the reduced/alkylated compound combined to LC-ESI-QTOF MS/MS analyses of reduced/alkylated fragment peptides following trypsin or V8 protease digestion. Results Using this two-step purification protocol combined to cell phenotypic screening, we identified a new toxin of 7329.38 Da (actiflagelin) that activates sperm motility in vitro from OF1 male mice. Actiflagelin is 63 amino acids in length and contains five disulfide bridges along the proposed pattern of disulfide connectivity C1-C5, C2-C3, C4- C6, C7-C8 and C9-C10. Modeling of its structure suggests that it belongs to the family of three finger toxins with a noticeable homology with bucandin, a peptide from Bungarus candidus venom. Conclusions This report demonstrates the feasibility of identifying profertility compounds that may be of therapeutic potential for infertility cases where motility is an issue.